179k views
2 votes
Which expression is equivalent to –8?

–2–3

(-1/2)^-3

(1/2)^-3

2–3

User Erik Pragt
by
5.7k points

2 Answers

4 votes

Answer:


((-1)/(2))^(-3) = -8.

Explanation:

Given : –8.

To find : Which expression is equivalent.

Solution : We have given –8.

By the radical rule :
((-1)/(x))^(-a) = -x^(a).

Then


((-1)/(2))^(-3) = -2^(3).


((-1)/(2))^(-3) = -8.

Therefore,
((-1)/(2))^(-3) = -8.

User Dmitrii Sorin
by
6.1k points
0 votes

Answer: second option. (NOTE: If the first option is
(-2)^3, then it would be an equivalent expression too, because:
(-2)(-2)(-2)=-8)

Explanation:

To solve this problem you must keep on mind the following exponents rule:


((1)/(a))^-b=a^b

Therfore, you have that:


(-(1)/(2))^-3=(-2)^3

This means that the number -2 must be multiply by itself three times. Therefore, you obtain the folllowing result:


(-2)(-2)(-2)=-8

If the first option is
(-2)^3, then it would be an equivalent expression too, because:


(-2)(-2)(-2)=-8

User Carkod
by
5.9k points